Kinetic equations in the theory of normal Fermi liquid - Kondratyev, A.S.; Siddique, I. (Физика низких температур, 2008)
On the bases of the improved approximation for the spectral function of one-particle states the Landau–
Silin kinetic equations for the normal Fermi liquids of neutral and electrically charged particles are
shown to be valid at finite temperature above the temperature of superfluid transition.